A review of the development of gangrene in patients with systemic lupus erythematosus – A 44-year follow-up study. (June 2023) - Rua, Joana; Isenberg, David
Objectives: This review addresses the question of what happens long-term to those systemic lupus erythematosus (SLE) patients who develop gangrene. It also seeks to find common clinical and serological features, risk factors and triggers and how best to manage this challenging complication. Methods: We reviewed 850 patients with SLE attending a UK tertiary referral center, followed up over 44 years, assessing their demographics, clinical and serological features, treatment in the acute phase, their long-term outcome and long-term management. Results: Ten out of 850 patients (1.2%) developed gangrene; the mean age of onset was 17 years (range 12–26 years) Eight out of 10 patients had a single episode of gangrene. One of the other two was not willing to have anticoagulation. The first episode of gangrene ranged from presentation to 32 years after SLE onset, mean duration of SLE at the onset of the gangrene was 18.5 years SD 11.5 years. Anti-phospholipid (PL) antibodies were over-represented in the patients with gangrene. All had active SLE at the time the gangrene developed. All patients were treated with intravenous (IV) iloprost infusions, and the antiphospholipid-antibody positive patients were anti-coagulated, most staying on long term anticoagulation. Underlying possible triggers were treated appropriately. Two patients who did not respond to the initial treatment needed further immunosuppression. All patients suffered digit loss. Conclusion: Although rare, gangrene is a sinister, potentially late developing complication of SLE, it rarely recurs. It is associated with anti-phospholipid antibodies, active disease, and other possible triggers such as infection and cancer. Anticoagulation therapy, steroids and iloprost, and further immunosuppression may be needed to stop the evolution of gangrene.